Penerapan Model Pembelajaran Problem Based Learning (PBL) dengan Bantuan Evaluasi Media Quizizz untuk Meningatkan Hasil Belajar Matematika - Siti Humaeroh; Junaidi; Afifah (Mataram University, 2025)
The purpose of this study was to improve mathematics learning outcomes on the topic of Three-Dimensional Shapes through the application of the Problem-Based Learning (PBL) model integrated with Quizizz media in Class VIII C of SMPN 7 Mataram. This research was conducted using a Classroom Action Research (CAR) method adapted from the Kemmis and McTaggart model and carried out in two cycles. Each cycle consisted of four main stages: planning, action implementation, observation, and reflection. The results showed that the implementation of the Problem-Based Learning (PBL) model combined with Quizizz media significantly improved the learning outcomes of Class VIII C students. Improvements were evident across various aspects, including average scores, highest and lowest scores, and the number of students achieving mastery. The average score increased from 71.85 in the pre-cycle to 78.92 in Cycle I, and further to 83.8 in Cycle II. Meanwhile, the percentage of students achieving mastery rose significantly from 50% in the pre-cycle to 80% in Cycle I, and reached 87.5% in Cycle II. These findings indicate that integrating PBL with Quizizz media is not only effective in enhancing students’ understanding of the material but also relevant and beneficial for modern educational contexts. This approach not only supports teachers in achieving cognitive learning objectives but also fosters the development of 21st-century skills such as critical thinking, creativity, collaboration, and communication.